Verifying the Environmental Kuznets Curve Hypothesis in the Case of India - Sultan, Zafar Ahmad; Yousef Alkhateeb, Tarek Tawfik; Adow, Anas Hamadelneel (International Journal of Energy Economics and Policy, 2021)
Growth with sustainability has nowadays become an important thrust area of world economy. The present paper has tried to examine the pollution-income relationship to verify the phenomenon of EKC hypothesis in the case of India for the period of 1978-2014. The application of Johansen cointegration method reveals that there is long run cointegration relationship between the two in the case of India. The study also validates the EKC hypothesis thus giving signal that India should pursue the strategy of “grow now and clean later”, a policy usually adopted by most of the rich countries of the world. Keywords: Environmental Kuznets Curve; Johansen cointegration; India. JEL Classifications: Q56, O53 DOI: https://doi.org/10.32479/ijeep.10392